2016
DOI: 10.1371/journal.pone.0165732
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Responses to Imbalanced Carbon: Nitrogen Availabilities in Rice Seedlings

Abstract: The internal C:N balance must be tightly controlled for the normal growth and development of plants. However, the underlying mechanisms, by which plants sense and balance the intracellular C:N status correspondingly to exogenous C:N availabilities remain elusive. In this study, we use comparative gene expression analysis to identify genes that are responsive to imbalanced C:N treatments in the aerial parts of rice seedlings. Transcripts of rice seedlings treated with four C:N availabilities (1:1, 1:60, 60:1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 138 publications
0
25
0
Order By: Relevance
“…This is consistent with the decreased CO 2 assimilation, maximum efficiency of light energy conversion (F v /F m ), and increased intercellular CO 2 and chlorosis symptom in O. sativa leaves under N limitation (Figs 1 and 3A-3C). Similarly, Huang et al (2016) reported that a chlorophyll a-b binding protein 2 (CAB2) encoding gene (Os01g0720500) was downregulated by low N [39]. The decreased photosynthesis is probably a direct effect of accumulated soluble carbohydrates and starch due to their metabolite feedback regulation, as revealed by increased contents of starch, sucrose and fructose in O. sativa leaves (Fig 3E and 3F).…”
Section: Plos Onementioning
confidence: 67%
See 1 more Smart Citation
“…This is consistent with the decreased CO 2 assimilation, maximum efficiency of light energy conversion (F v /F m ), and increased intercellular CO 2 and chlorosis symptom in O. sativa leaves under N limitation (Figs 1 and 3A-3C). Similarly, Huang et al (2016) reported that a chlorophyll a-b binding protein 2 (CAB2) encoding gene (Os01g0720500) was downregulated by low N [39]. The decreased photosynthesis is probably a direct effect of accumulated soluble carbohydrates and starch due to their metabolite feedback regulation, as revealed by increased contents of starch, sucrose and fructose in O. sativa leaves (Fig 3E and 3F).…”
Section: Plos Onementioning
confidence: 67%
“…Here, our RNA-Seq data showed that the expression levels of genes such as anthocyanidin reductase, bisdemethoxycurcumin synthase-like, chalcone synthase (CHS), chalcone-flavonone isomerase (CHFI), flavanone 3-dioxygenase 2-like, etc., which implicated in flavonoids biosynthesis were apparently upregulated by N deficiency in O. sativa leaves (S4 and S5 Tables; Fig 5). Huang et al (2016) also reported that the expression level of CHS was induced by low N in rice by microarray hybridization technique [39]. Peng et al reported that N limitation could channel the phenylpropanoid metabolic flux to the induced anthocyanin synthesis, which facilitated the adaptation of Arabidopsis seedlings to N limitation [67].…”
Section: N Deficiency Increased the Degs Involved In Flavonoid Biosynmentioning
confidence: 99%
“…Transcription factors are important for controlling the expression of other genes in plant exposed to limited N condition or in complete starvation (Krapp et al ., 2011; Yang et al ., 2015; Curci et al ., 2017) and, accordingly, our results showed as the regulation of transcripts was highly different and, in some case, with an opposite trend between emmer and durum wheat. In addition, some GO categories were only enriched for the DEGs in durum wheat, such as: the cellular amino acids, oxoacid or organic acids metabolism which were also highlighted by Huang et al (2016) in their study on the transcriptomic evaluation in response to the imbalance of carbon: nitrogen ratio in rice seedling.…”
Section: Discussionmentioning
confidence: 99%
“…For root NRT2s genes and HATS activity in Arabidopsis , it enabled the identification of CIPK23 and CIPK8 in response to NO 3 - , LBDs transcription factors in response to high N and BT2, a negative regulator of NRT2.1 and NRT2.4 under low N conditions (Figure 7) (Ho et al, 2009; Hu et al, 2009; Rubin et al, 2009; Araus et al, 2016). For C and N signaling, previous microarray studies in response to transient treatments with NO 3 - , sucrose or NO 3 - plus sucrose have been used to reveal, at the level of the genome, the existence of interaction between C and N signaling (Wang et al, 2003; Price et al, 2004; Scheible et al, 2004; Wang et al, 2004; Gutierrez et al, 2007; Huang et al, 2016). In Arabidopsis, over 300 genes have been found differentially expressed by combined C:N treatments compared to C or N treatments (Palenchar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%